(untitled) (Journal of the College of Basic Education, 2024)
The importance of the research came in developing exercises using rubber bands, which are characterized by an increase in the degree of resistance against which the working muscles work as the range of motion in the central contraction increases, as the elastic resistance used in the exercise is characterized by the degree of resistance it generates increasing the more the rubber band is stretched while performing the central movement of the exercise. Which requires increasing the intensity of muscle contraction against the resistance used or the weight used in the exercise throughout the range of motion so that the movement can be completed, and muscle stimulation of the working muscles can be achieved with a greater degree of effectiveness at all points of the motor path of the central movement of the exercise, and the more the athlete becomes able to produce force. The closer the central movement is to its end, the higher the level of resistance faced by the working muscles, the closer the central movement is to its end. Rubber bands also work to generate resistance during eccentric contraction and return to the original position. The study aimed to prepare suggested exercises using rubber bands to develop some health fitness variables. For female students, and to identify the effect of exercises suggested using rubber bands on some variables of health fitness for female students. The researcher used the experimental approach in the style of the control and experimental groups with a pre- and post-test to suit the nature of the research and its objectives. The researcher chose the research community in an intentional way, and the research community was represented by female students of the second stage/college. Physical education and sports sciences for girls / University of Baghdad, for the academic year (2023 - 2024), numbering (40) female students. The researcher chose (20) female students from a total of (40) as a sample of the research, then chose (10) female students by lottery to represent the experimental group. And (10) female students to represent the control group. The field research procedures included conducting experiments and tests on some components of health fitness, which included (upper arm circumference, chest circumference, waist circumference, hip circumference, thigh circumference, Brash cardiac energy index, flexibility test, compatibility test, test Balance), these exercises were applied within the main section of the test and took 45-50 minutes at a rate of (2) units per week for (8) weeks, as the number of training units reached (16) units. In light of the results obtained by the researcher, the researcher concluded Exercising using rubber bands has a positive effect in developing some components of health fitness. The researcher recommends the necessity of adopting fitness programs for health for female athletes and those who do not practice sports activity, and the necessity of using rubber bands because of its positive impact in improving health fitness